2007
DOI: 10.1103/physrevlett.99.055502
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pressure on the Boson Peak: Stronger than Elastic Medium Transformation

Abstract: We study the changes in the low-frequency vibrational dynamics of poly(isobutylene) under pressure up to 1.4 GPa, corresponding to a density change of 20%. Combining inelastic neutron, x-ray, and Brillouin light scattering, we analyze the variations in the boson peak, transverse and longitudinal sound velocities, and the Debye level under pressure. We find that the boson peak variation under pressure cannot be explained by the elastic continuum transformation only. Surprisingly, the shape of the boson peak rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
120
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(144 citation statements)
references
References 27 publications
24
120
0
Order By: Relevance
“…When plotted as C(T)/T 3 vs T (Figure 2), the specific heat for all the studied samples evidences the characteristic shape for a glass determined by an upturn below 2 K and a broad peak above 2 K. Growing densification depresses C(T) over the whole temperature interval explored giving rise to a significant decrease of the hump and to an increase of the peak temperature T peak , which shifts from about 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 that all the vibrational modes, extended and quasi-localized, contributing to the hump form a distribution which is independent of density. Both the observations discussed above are in agreement with the results of studies concerning the low temperature specific heat in compacted SiO 2 [11] and in situ high pressure inelastic neutron scattering measurements on poly-isobutylene (PIB) [21,22]. Even if, as pointed out in SiO 2 [23], measurements with in situ applied pressure cannot be simply compared to the observations in permanently densified samples retrieved from the same interval of pressure, these results concerning the low energy vibrational dynamics appear to be quite general and independent of the specific experimental conditions.…”
Section: Resultssupporting
confidence: 81%
“…When plotted as C(T)/T 3 vs T (Figure 2), the specific heat for all the studied samples evidences the characteristic shape for a glass determined by an upturn below 2 K and a broad peak above 2 K. Growing densification depresses C(T) over the whole temperature interval explored giving rise to a significant decrease of the hump and to an increase of the peak temperature T peak , which shifts from about 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 that all the vibrational modes, extended and quasi-localized, contributing to the hump form a distribution which is independent of density. Both the observations discussed above are in agreement with the results of studies concerning the low temperature specific heat in compacted SiO 2 [11] and in situ high pressure inelastic neutron scattering measurements on poly-isobutylene (PIB) [21,22]. Even if, as pointed out in SiO 2 [23], measurements with in situ applied pressure cannot be simply compared to the observations in permanently densified samples retrieved from the same interval of pressure, these results concerning the low energy vibrational dynamics appear to be quite general and independent of the specific experimental conditions.…”
Section: Resultssupporting
confidence: 81%
“…In some systems, 14,18,19 it appears that the BP variation is solely associated with the change in the Debye frequency, which accounts for the modifications of the elastic continuum medium. In other cases, 13,[15][16][17] the BP shifts more strongly than suggested by the simple variation of the macroscopic medium. Specifically, this second behavior is observed when the system is subjected to an important volume change, of the order of 10% to 20%.…”
Section: Introductionmentioning
confidence: 97%
“…Among them we may recall the soft potential model, 4 the mode-coupling theory applied to the vibrations in glasses, 5 models on a lattice 6 or on the continuum 7 with randomly fluctuating elastic constants, and harmonic models where the atoms vibrate around topologically disordered configurations. 8,9 Experimentally the BP has been studied as a function of macroscopic parameters such as the temperature, 10,11 the density, [12][13][14][15] and the pressure 16,17 or during chemical vitrification 18 or as a function of the quenching rate. 19 It is observed that the BP shifts to higher frequencies and decreases in intensity when the pressure or the density is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Data were reduced by DAVE [26]. The boson peak is a broad peak observed at frequencies ∼2-10 meV in the inelastic neutron [27][28][29][30][31], nuclear inelastic [32][33][34][35], and Raman [36][37][38][39] scattering spectra of disordered materials and supercooled liquids. Its origin is widely believed to be related to the transverse dynamics of the material [32][33][34]40,41].…”
mentioning
confidence: 99%